Long-term multidimensional health status of individuals with and without post COVID-19 condition: A cross-sectional study - Debbie Gach; Frits H. M. van Osch; Joop P. van den Bergh; Rein Posthuma; Hester A. Gietema; Martijn D. de Kruif; Annemie M. W. J. Schols; Rosanne J. H. C. G. Beijers (PLoS ONE, 2026)
Post COVID-19 condition (PCC) significantly affects health-related quality of life (HRQoL), but involvement and interconnectivity of different health dimensions is still underexplored. This study aims to characterize the multidimensional health status of individuals with and without PCC after at least one year follow-up. Hospitalized and non-hospitalized COVID-19 patients were included from three hospitals in the Netherlands. HRQoL, pulmonary and metabolic health, muscle strength, physical capability, symptoms, psychological- and social wellbeing, and cognitive function were measured using validated objective and subjective methodology. Presence of PCC was based on self-report. 139 participants were included, of which 87 with PCC and 52 without PCC. HRQoL was lower in the PCC group compared to the non-PCC group (EQ-5D: p = 0.005; VAS: p < 0.001). Individuals with PCC also more frequently reported fatigue, anxiety/depression, stress and loneliness, alongside lower subjective cognitive functioning and sleep quality ( p < 0.05). Inspiratory muscle strength and exercise capacity ( p = 0.024 and p = 0.007) were lower in the PCC group than the non-PCC group. Pulmonary function and residual CT-abnormalities, body composition, cardiometabolic risk, expiratory- and peripheral muscle strength, mobility, physical activity, and cognitive function tests were not different between groups. Perceived health burden in PCC is reflected by lower health status, more frequently reported symptoms of fatigue and poor sleep quality, and lower psychological- and social wellbeing and subjective cognitive functioning compared to non-PCC. These differences are only partially reflected in objectively assessed dimensions of muscle strength and physical capability, but not in pulmonary/metabolic health and cognitive function. The findings indicate a discordance between subjective health burden and currently available objective assessments in individuals with PCC.